773Triple elimination of mother-to-child transmission of HIV, syphilis and hepatitis B in the Pacific Islands. (2nd September 2021) - Van Gemert, Caroline; Hellard, Margaret; Howell, Jess; O'Connor, Michelle; Cowie, Ben; Allard, Nicole; Homer, Caroline; Brink, Anne; Chan, Po-Lin; Kaldor, John; Hockin, Jane
Abstract: Background: Without intervention, HIV, hepatitis B virus and syphilis can be transmitted from mother-to-child during pregnancy, birth and breastfeeding and these can cause adverse pregnancy and longer-term outcomes. The 22 Pacific Island countries and territories (PICTs) have among the highest global prevalence of syphilis and hepatitis B. Mother-to-child transmission remains a concern, particularly hepatitis B. Global and regional elimination targets have been set to eliminate mother-to-child transmission (EMTCT) however progress of PICTs towards meeting targets is unknown. Methods: Data from 2000-2019 relating to EMTCT epidemiological, process and impact targets were extracted from peer reviewed literature, online data repositories and grey literature. Results: 27 peer reviewed reports, data from online data repositories for 19 countries and twelve national demographic and/or health reports were collated. Existing online databases report data for only small number of EMTCT indicators and there are few peer-reviewed studies that report EMTCT coverage estimates for PICTs. Availability of data varied between countries and available data suggests that few countries are meeting EMTCT indicator targets. Conclusions: Based on the current trach trajectory, PICTs will not reach triple elimination by 2030. Both interventions to improve EMTCT activity coverage and strengthened surveillance, monitoring and evaluation systems are required. Key messages: Mother-to-child transmission of HIV, hepatitis B and syphilis is a major concern in the Pacific and increased efforts are required, including strengthened monitoring and evaluation systems.